The new absolutes - Watkins, William D. (Minneapolis, MN Bethany, 1996)
Includes bibliographical references and index.
Keywords: Apologetics; Skepticism -- controversial literature; Relativity -- controversial literature; Moral conditions; Civilisation. modern -- 20th century